Dairy profitability simulator mobile application: IPSR Innovation Profile - Rao, E.J.O.; Ojango, Julie M.K.; Menjo, Dominic; Kang'ethe, Edwin; Kipkosgei, Gideon; Mogaka, David; Jabes, Yusuf (2022)
The Dairy profitability simulator is a mobile application that integrates practical and scientific knowledge in an algorithm that projects the expected annual production and profitability of the small-holding enterprise based on known input variables affordable and accessible to the smallholder farmer. The application reveals to the smallholders, the inputs, services and practices that need to be adjusted to ensure profitability of their enterprise. It also enables structured engagement between extension service providers and farmers and enables targeted advisory services to smallholders.